Sodium butyrate alleviates R97-116 peptide-induced myasthenia gravis in mice by improving the gut microbiota and modulating immune response - Jing Sun; Juanjuan Chen; Qinfang Xie; Mengjiao Sun; Wenjing Zhang; Hongxia Wang; Ning Liu; Qi Wang; Manxia Wang (BMC, 2023)
Abstract Fermented butyrate exhibits an anti-inflammatory response to maintain immune homeostasis within the gut. However, the effect and underlying mechanism of butyrate on myasthenia gravis (MG) remain unclear. The changes in the gut microbiota and fecal contents of SCFAs in MG patients were examined. R97-116 peptide was used to induce the experimental autoimmune myasthenia gravis (EAMG) mice and sodium butyrate (NaB) was gavaged to the EAMG mice. Gut microbiota, the frequency of Th1, Th17, Treg, Tfh, and B cells, the levels of IFN-γ, IL-17 A, IL-10, IL-21, and anti-R97-116 IgG, RNA-seq of total B cells in the spleen were explored by metagenomics, flow cytometry, ELISA, and transcriptomics. A significant reduction in SCFA-producing bacteria including Butyricimonas synergistica and functional modules including butyrate synthesis/production II was observed in MG patients and fecal SCFAs detection confirmed the increase. The EAMG mice were successfully constructed and NaB supplementation has changed the composition and function of the gut microbiota. The numbers of Th1, Th17, Tfh, and B cells were significantly increased while that of Treg cells was obviously decreased in EAMG mice compared with controls. Interestingly, NaB treatment has reduced the amounts of Th17, Tfh, and B cells but increased that of Treg cells. Accordingly, the levels of IL-17 A, IL-21, and IgG were increased while IL-10 was decreased in EAMG mice. However, NaB treatment reduced IL-17 A and IL-21 but increased that of IL-10. RNA-seq of B cells has revealed 4577 deferentially expressed genes (DEGs), in which 1218 DEGs were up-regulated while 3359 DEGs were down-regulated in NaB-treated EAMG mice. GO enrichment and KEGG pathway analysis unveiled that the function of these DEGs was mainly focused on immunoglobulin production, mitochondrial respiratory chain complex, ribosome, oxidative phosphorylation, and CNS diseases including amyotrophic lateral sclerosis. We have found that butyrate was significantly reduced in MG patients and NaB gavage could evidently improve MG symptoms in EAMG mice by changing the gut microbiota, regulating the immune response, and altering the gene expression and function of B cells, suggesting NaB might be a potential immunomodulatory supplement for MG drugs.